Changes in the Procedure for Registration of Non-Profit Organizations - Radev, Stefan (Research Papers, 2020)
The article discusses changes in the registration procedure for associations and foundations. The purpose of the work is to analyze the specifics of the current regulatory framework, with the following tasks to achieve it: a description of the effect of registration and a comparison of the similarities and differences between the new and old regulations. The methods of analysis and comparison are applied. As a result, the main points of the current procedure are outlined and conclusions about its positive effect systematized and outlined in a single article.
Keywords: Non-profit organization; Register; Prodecure